Comparison of VPN Protocols at Network Layer Focusing on Wire Guard Protocol - Abdulazeez, Adnan Mohsin; Salim, Baraa Wasfi; Zeebaree, Diyar Qader; Doghramachi, Dana (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The key point of this paper is to assess and look over the top of the line network layer-based VPN (Virtual Private Network) protocols because data link layer is hardly ever found to be in use in organizations, the reason is because of its exceedingly high charge. Virtual Private Network (VPN) is commonly used in business situations to provide secure communication channels over public infrastructure such as Internet. Virtual Private Networks (VPNs) provide a secure encrypted communication between remote networks worldwide by using Internet Protocol (IP) tunnels and a shared medium like the Internet. The paper follows and sets standards for different types of protocols and techniques, the VPN (Virtual Private Network) architectural feature is made to deliver dependable and safe network that is not in line with regular networks that provide a higher trust and a higher secure channel between user and organization. The current study took place to summaries the usage of existing VPNs protocol and to show the strength of every VPN. Through different studies that have been made by other researchers as well as an extra focus on the state of art protocol, Wire guard. It is also worthy to mention that wire guard compared with other protocols such as IPsec and GRE. The studies show the WireGuard being a better choice in terms of other well-known procedures to inaugurate a secure and trusted VPN.